Quantitative Sulphur Estimation: Fast Method Using Microwave Irradiation - Nagpurkar, L.P.; Jachak, M.M.; Ekhe, J.D. (Asian Journal of Chemistry, 2010)
Sulphur estimation is very much important to the synthetic chemists and quality controllers of various industrial products. Although, there have been various methods for the quantitative estimation of sulphur in organic compounds, some of them involve complete degradation and gravimetric measurement of sulphur as barium sulphate. The time required for the actual degradation by normal heating is very high, which has been considerably reduced using microwave irradiation. In present work, the safe use of modified microwave oven, satisfactory and faster quantitative sulphur measurement has been discussed. This method has established its time saving potential over normal sulphur estimation. Wide variety of high purity chemicals have been tested for its sulphur content